Standing in the breach an Old Testament theology and spirituality of intercessory prayer - Widmer, Michael 1970- (Winona Lake, Indiana Eisenbrauns, 2015)
Hermeneutical reflections -- Abraham: patriarch and intercessor (Genesis 18) -- Moses: Israel's archetypal intercessor (Exodus 17, 32-34, Numbers 13-14, Deuteronomy 9-10) -- Samuel: Israel's second legendary intercessor (1 Samuel 7, 12, 15) -- David: repentant sinner, priestly intercessor, and YHWH's change of mind (2 Samuel 24) -- Solomon: prayer of dedication (1 Kings 8) -- The suffering servant: substitutionary atonement through intercession (Isaiah 53) -- Jeremiah: agent of grace and judgment -- Joel: the people's repentance, priestly intercession, and God's gracious return (Joel 2) -- Amos: the logic of intercessory prayer (Amos 7) -- Summary of theological findings and some implications.
Includes bibliographical references. - Print version record and CIP data provided by publisher
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Theology -- Bible; Bible -- Theology; Bible; Intercessory prayer -- Biblical teaching; Intercessory prayer -- Biblical teaching; RELIGION ; Christian Life ; General; Intercessory prayer ; Biblical teaching; Theology; Electronic books